Respiratory manifestations of malaria. - Taylor, W; Hanson, J; Turner, G; White, N; Dondorp, A (2012)
Respiratory distress develops in up to 25% of adults and 40% of children with severe falciparum malaria. Its diverse causes include respiratory compensation of metabolic acidosis, noncardiogenic pulmonary edema, concomitant pneumonia, and severe anemia. Patients with severe falciparum, vivax, and knowlesi malaria may develop acute lung injury (ALI) and ARDS, often several days after antimalarial drug treatment. ARDS rates, best characterized for severe Plasmodium falciparum, are 5% to 25% in adults and up to 29% in pregnant women; ARDS is rare in young children. ARDS pathophysiology centers on inflammatory-mediated increased capillary permeability or endothelial damage leading to diffuse alveolar damage that can continue after parasite clearance. The role of parasite sequestration in the pulmonary microvasculature is unclear, because sequestration occurs intensely in P falciparum, less so in P knowlesi, and has not been shown convincingly in P vivax. Because early markers of ALI/ARDS are lacking, fluid resuscitation in severe malaria should follow the old adage to "keep them dry." Bacteremia and hospital-acquired pneumonia can complicate severe malaria and may contribute to ALI/ARDS. Mechanical ventilation can save life in ALI/ARDS. Basic critical care facilities are increasingly available in tropical countries. The use of lung-protective ventilation has helped to reduce mortality from malaria-induced ALI/ARDS, but permissive hypercapnia in unconscious patients is not recommended because increased intracranial pressure and cerebral swelling may occur in cerebral malaria. The best antimalarial treatment of severe malaria is IV artesunate.